Validation of rubric for evaluation of e-activities designed for achievement of digital teaching competences - Marcano, Beatriz (2020)
Due to the importance of developing digital teaching competencies in the teacher training processes, e-activities were designed in order to increase the functionality of these competences and to be evaluated through rubrics. Therefore, the objective of this study is to verify the validity of the rubrics in order to assess the digital teaching competence and their respective effectiveness, according to the model of the National Institute of Educational Technologies and Teacher Training in Spain. To this end, a two-phase validation procedure was implemented: one by expert judgment, in which the correspondence of the rubrics with the indicators of digital teaching competence had to be corroborated and another phase of empirical validation to validate the efficiency of the rubrics for e-activity corrections, corrected by three teachers. In this phase, a mean difference analysis was performed (Friedman's Test at the 0.05 level) and it was found that there were no significant differences between the correctors who were not the teacher of the subject. Furthermore, it was concluded that the rubrics were valid to check the evaluated digital teaching competences.